Embossed TiO2 Thin Films with Tailored Links between Hollow Hemispheres: Synthesis and Gas-Sensing Properties - Moon, Hi Gyu; Shim, Young-Seok; Su, Dong; Park, Hyung-Ho; Yoon, Seok-Jin; Jang, Ho Won (American Chemical Society, 2011)
Embossed TiO2 thin films with high surface areas were achieved using soft templates composed of monolayer polystyrene beads. The structure of links between beads in the templates could be controlled by varying O-2 plasma etching time, resulting in a variety of templates with close-linked, nanolinked, or isolated beads. Room-temperature deposition of TiO2 on the plasma-treated templates and calcination at 550 degrees C resulted in embossed films with tailored links between anatase TiO2 hollow hemispheres. Although all embossed TiO2 films displayed a similar increase in the surface-to-volume ratio compared with a plain TiO2 thin film, the response of embossed TiO2 films with nanolinked hollow hemispheres to CO or ethanol gases was much higher than the response of films with close-linked or isolated. hollow hemispheres. The strong correlation between gas sensitivity and the structure of links between the TiO2 hollow hemispheres revealed the critical importance of tailoring links between individual oxide nanostructures for enhancing gas-sensing properties of the ensemble of the individual nanostructures. The facile and large-scale synthesis of embossed TiO2 films with nanolinked hollow hemispheres on Si substrates and the high sensitivity that is achieved without the aid of additives provide a sustainable competitive advantage over other methods for fabricating highly sensitive metal oxide gas sensors.
Keywords: SENSOR APPLICATIONS; HYDROGEN SENSOR; METAL-OXIDES; TEMPLATES; NANOBELTS; NANOWIRES; NANOSTRUCTURES; PERFORMANCE; FABRICATION; NANOFIBERS